2018
DOI: 10.1186/s12866-018-1259-8
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa responds to exogenous polyunsaturated fatty acids (PUFAs) by modifying phospholipid composition, membrane permeability, and phenotypes associated with virulence

Abstract: BackgroundPseudomonas aeruginosa, a common opportunistic pathogen, is known to cause infections in a variety of compromised human tissues. An emerging mechanism for microbial survival is the incorporation of exogenous fatty acids to alter the cell’s membrane phospholipid profile. With these findings, we show that exogenous fatty acid exposure leads to changes in bacterial membrane phospholipid structure, membrane permeability, virulence phenotypes and consequent stress responses that may influence survival and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 83 publications
0
45
4
Order By: Relevance
“…2). Compared to other similarly performed analyses from our laboratory [1][2][3][4], the migratory shifts were much less pronounced, suggesting a lower degree of PUFA incorporation. Subsequent UPLC/MS analyses con rmed at least some degree of incorporation of all fatty acids except 22:6 into PE and PG.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…2). Compared to other similarly performed analyses from our laboratory [1][2][3][4], the migratory shifts were much less pronounced, suggesting a lower degree of PUFA incorporation. Subsequent UPLC/MS analyses con rmed at least some degree of incorporation of all fatty acids except 22:6 into PE and PG.…”
Section: Discussioncontrasting
confidence: 79%
“…No longer are fatty acids merely a carbon source destined for b-oxidation; they represent multipurpose molecules capable of nutritional value, membrane phospholipid remodeling, and signalmediated behavioral control. Previous studies from our laboratory have explored these phenomena in several medically important bacteria, including Vibrio species, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Acinetobacter baumanii [1][2][3][4]; however, an analysis of the model organism E. coli had not been performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to their hydrophobic nature, lipids are engaged in different types of interactions with AuNPs and AgNPs. For example, in a report published by Bakri et al, the authors proposed interactions of lipid-coated AuNPs with the biomembrane of bacteria [ 65 ]. They used 1,2-distearoyl-sn-glycero-3-phosphorylethanolamine-coated gold nanorods (DSPE-AuNRs) against P. aeruginosa and suggested that DSPE interacts with bacterial lipid membrane via hydrophobic interactions and destabilizes it ( Figure 5 A,B).…”
Section: Interaction Of Gold and Silver Nanoparticles With Biofilmmentioning
confidence: 99%